A method for thermal post stabilization of paper-based lenticular raster pictures

CN122956866APending Publication Date: 2026-10-23GUANGDONG SHENGQI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611308290.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,现有的交联反应严重依赖高温触发,通常需要160℃至180℃的高温焙烘才能完成酯化交联,其深层症结在于干燥纸页中纤维素无定形区处于玻璃化冻结状态,羟基又被致密氢键网络锁闭,反应实际受基体迁移率与羟基可及性而非本征化学能垒所限,不得不以远超化学需求的高温换取链段解冻

Benefits of technology

首先,本发明缓解了纸基纤维交联改性所需的高温条件与光栅透镜材料热敏特性之间的冲突。二甲基砜作为氢键破坏剂与次磷酸钠的脱水催化协同作用,使多元羧酸交联反应的表观活化能显著下降,将深度酯化交联的触发温度降至95℃至105℃区间;同时,覆置于透镜面的离型层与柔性均压缓冲垫将保压载荷以近似静水压的形式贴服传递至透镜曲面,使热与力两方面的损伤驱动同时受到抑制。由此,柱镜光栅的折射微结构在整个后稳定化处理过程中不发生热塌陷或熔融变形,微米级的光学对位精度得以保持,纸张在温湿度变化下的翘曲及由此引起的光学重影与像差得到有效控制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956866A_ABST
    Figure CN122956866A_ABST
Patent Text Reader

Abstract

The application discloses a kind of paper-based lenticular grating picture heat post-stabilization processing method.This method prepares slightly acidic pre-impregnation stabilization liquid by multi-carboxylic acid crosslinking agent, phosphorus-containing catalyst, dimethyl sulfone, multi-functionality water-soluble epoxy resin and pre-hydrolyzed epoxy silane coupling agent, glues paper base material and gradient pre-dries below esterification crosslinking activation temperature;After printing interlaced microimage sequence, coating water-based polyurethane adhesive and cold pressing with lenticular grating sheet, two-stage low-temperature heat post-curing is carried out: the first stage makes silanol group and cellulose hydroxyl group dehydrate condensation, and the second stage triggers esterification crosslinking, ring-opening etherification and covalent addition of epoxy group and adhesive active group simultaneously at 100 DEG C to 110 DEG C under the action of hydrogen bond destruction of dimethyl sulfone and catalysis of phosphorus-containing catalyst under the mechanical pressure of flexible uniform pressure buffer pad, to build semi-interpenetrating network.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of paper-based printed packaging and optical anti-counterfeiting product manufacturing technology, and in particular to a method for thermal post-stabilization treatment of paper-based cylindrical lens grating images. Background Technology

[0002] Lenticular lenticular printing, as an optical printing product capable of producing strong visual impact effects such as three-dimensional depth, dynamic transformations, and flip animations, relies on the core optical mechanism of precise optical refraction between the interlaced micro-image sequence printed on the underlying substrate and the cylindrical lens array covering the surface. To ensure the accuracy of the optical effect, the pitch of the lenticular material must achieve absolute alignment with the lines of the underlying printing ink at the micrometer level. Extremely small dimensional deviations or minute warping deformations of the substrate material can cause severe optical aberrations, ghosting, or viewing angle deviations. In recent years, with the global trend of replacing plastic with paper, the use of paper made from natural cellulose to completely or partially replace the original pure polyethylene terephthalate (PET) or polyvinyl chloride (PVC) substrates has become an inevitable direction for the industry.

[0003] However, when combining highly hygroscopic paper-based materials with thermoplastic polymer gratings, irreconcilable thermodynamic and kinetic contradictions exist within the existing technological framework, leading to two core technical problems. First, the paper-based material contains a large number of free hydroxyl groups, giving it extremely strong hygroscopicity. When the ambient temperature and humidity fluctuate, the penetration or loss of water molecules can break the intramolecular and intermolecular hydrogen bond network of cellulose molecules, causing irreversible swelling or shrinkage of the matrix. Due to the order-of-magnitude difference between the thermal expansion coefficients and hygroscopic expansion coefficients of the paper and the surface plastic grating, the huge shear thermal stress and hygroscopic stress accumulated between the layers can cause paper warping, directly compromising the micron-level optical alignment accuracy. Second, to improve the dimensional stability of the paper, the conventional approach in this field is to use polycarboxylic acids (such as 1,2,3,4-butanetetracarboxylic acid) to crosslink and modify cellulose, constructing a stable three-dimensional covalent network. However, existing crosslinking reactions heavily rely on high-temperature triggering, typically requiring high-temperature baking at 160°C to 180°C to complete esterification crosslinking. The underlying problem is that the amorphous regions of cellulose in the dried paper are in a glassy frozen state, and the hydroxyl groups are locked by a dense hydrogen bond network. The actual reaction is limited by the matrix mobility and hydroxyl accessibility rather than the intrinsic chemical energy barrier, so high temperatures far exceeding chemical requirements are used to thaw the chain segments. The glass transition temperature of cylindrical lens grating materials is generally between 70°C and 80°C. Above this range, the material modulus drops sharply by two to three orders of magnitude, entering a highly elastic state. The bulk viscosity continues to decrease by orders of magnitude as the temperature rises further. Under baking conditions of 160°C to 180°C, the cylindrical lens array, which is close to a flow dynamic, undergoes irreversible thermal collapse and optical structural damage within tens of seconds. If the baking temperature is simply reduced, the esterification conversion of the conventional catalytic system stalls rapidly below 140°C. When a rigid pressure plate directly presses against the lens protrusion, which is still in a highly elastic state, the concentration of contact stress will also cause crushing of the tooth tip. The process windows of these two factors cannot be reconciled within the existing technological framework. If the base paper is first subjected to high-temperature heavy cross-linking and then laminated, the cross-linked paper fibers will exhibit extreme rigidity and embrittlement. Furthermore, the surface-active hydroxyl groups are largely consumed and blocked by the dense esterification network, and the remaining strong acidic sites will continue to catalyze the hydrolysis of ester bonds and urethane bonds in the adhesive. Wetting adhesion and service durability deteriorate simultaneously, easily leading to delamination failure between the paper and plastic layers. There is a need in this field for a new approach to resolve the aforementioned contradictions. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for the thermal stabilization of paper-based cylindrical lens gratings. By combining in-situ pre-impregnation with low-temperature thermal curing, the chemical cross-linking of the paper matrix and the covalent bonding of the paper-plastic interface are achieved in a lower temperature range without damaging the optical microstructure.

[0005] According to one aspect of the present invention, in the step of preparing the pre-impregnation stabilizing solution, a polycarboxylic acid crosslinking agent, a phosphorus-containing catalyst, dimethyl sulfone, a multifunctional water-soluble epoxy resin, and a pre-hydrolyzed epoxy silane coupling agent are mixed in an aqueous medium, and the pH of the mixture is adjusted to be slightly acidic. The purpose of controlling the slightly acidic environment is to maintain most of the carboxylic acid groups in the molecular structure of the polycarboxylic acid crosslinking agent in a non-dissociated protonated state, which is a prerequisite for the subsequent formation of internally dehydrated cyclic anhydrides. Simultaneously, this environment can inhibit irreversible intermolecular self-condensation of the hydrolyzed silanol groups, maintaining the chemical activity of the system. Furthermore, by adjusting the pH value before preparation and then adding the multifunctional water-soluble epoxy resin and the pre-hydrolyzed epoxy silane coupling agent at room temperature, and by using the pre-impregnation stabilizing solution immediately after preparation, the acid-catalyzed hydrolysis of epoxy groups in the slightly acidic aqueous phase can be suppressed to a very low level, ensuring that they are sealed in an active state until the post-heat curing stage.

[0006] Preferably, in the pre-impregnation stabilizing solution, the polycarboxylic acid crosslinking agent is 1,2,3,4-butanetetracarboxylic acid, the phosphorus-containing catalyst is selected from sodium hypophosphite or sodium hypophosphite monohydrate, the multifunctional water-soluble epoxy resin is a polyglycerol polyglycidyl ether with an aliphatic backbone and at least four epoxy groups, and the pre-hydrolyzed epoxysilane coupling agent is prepared by hydrolysis of γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The use of 1,2,3,4-butanetetracarboxylic acid provides dense carboxyl crosslinking sites, while the long-chain polyether backbone of polyglycerol polyglycidyl ether has good conformational flexibility. After embedding in the rigid crosslinking network, it can absorb and dissipate internal stress caused by temperature and humidity changes, reducing the brittleness caused by heavy crosslinking of cellulose.

[0007] More preferably, based on 1000 parts by mass of the aqueous medium, the addition amounts of each component are as follows: 60 to 70 parts by mass of the polycarboxylic acid crosslinking agent, 40 to 50 parts by mass of the phosphorus-containing catalyst, 10 to 20 parts by mass of dimethyl sulfone, 20 to 30 parts by mass of the multifunctional water-soluble epoxy resin, and 10 to 15 parts by mass of the pre-hydrolyzed epoxy silane coupling agent (calculated as effective pure material). The pH of the mixture is adjusted to the range of 2.8 to 3.2 by adding alkali. If the amount of dimethyl sulfone is less than 10 parts by mass, its concentration is insufficient to fully penetrate the amorphous region to break the intramolecular and intermolecular hydrogen bonds of cellulose, making it difficult to reduce the steric hindrance of the reaction system; if it is more than 20 parts by mass, excessive free phase residue will trigger reverse plasticization, leading to the collapse of the paper's structural strength. The choice of dimethyl sulfone, rather than a liquid strong hydrogen bond acceptor solvent, is also due to its odorless and low-toxicity solid nature, which aligns with food contact compliance requirements for paper-based packaging. With a melting point of approximately 109°C, it can remain intact within the paper base without any volatilization loss after pre-drying, achieving sufficient molecular migration capability by remaining near the molten state within the heat-curing window. Strictly maintaining the pH value between 2.8 and 3.2 is to ensure the protonation rate of 1,2,3,4-butanetetracarboxylic acid while avoiding irreversible catalytic degradation of cellulose polymerization caused by excessive acidity.

[0008] Preferably, the pre-hydrolyzed epoxy silane coupling agent is prepared by the following process: γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added dropwise to deionized water with the pH adjusted to 4.0 using acid, and the mixture is stirred and hydrolyzed at room temperature for 30 to 45 minutes until the mixture changes from turbid to a transparent homogeneous solution. A pH of 4.0 is the kinetic optimal condition for the hydrolysis of methoxy groups into active silanol groups, which ensures complete hydrolysis and releases active groups for subsequent interfacial bridging.

[0009] According to one aspect of the invention, in the in-situ micro-impregnation and sub-activation pre-drying step, the paper substrate is impregnated in the aforementioned pre-impregnation stabilizing liquid for sizing treatment. Preferably, the sizing treatment is performed using a two-roll press sizing machine, and the linear pressure of the sizing rolls is controlled to maintain the liquid carryover rate of the paper substrate at 75% to 80%. Too low a liquid carryover rate will prevent the crosslinking agent from fully penetrating to the deep layers of the matrix; too high a liquid carryover rate will cause component surface migration and enrichment during subsequent drying, affecting subsequent printing adhesion.

[0010] More preferably, the maximum drying temperature of the gradient pre-drying does not exceed 80°C, and the absolute moisture content of the paper substrate is controlled at the drying endpoint to be between 4.0% and 5.5%. Strictly limiting the maximum temperature to below 80°C maintains the system below the esterification crosslinking activation temperature, ensuring that the polycarboxylic acid crosslinking agent does not undergo substantial esterification crosslinking. The silane component only completes pre-anchoring through hydrogen bond adsorption and a small number of primary condensation sites, retaining its main condensation capacity, thereby preserving the paper's excellent smoothness and ink absorbency. Controlling the moisture content between 4.0% and 5.5% removes free water that affects the initial tack of the adhesive while retaining an appropriate amount of bound water to maintain the paper's flexibility and prevent the paper from becoming brittle and powdery due to over-drying.

[0011] According to one aspect of the present invention, in the printing and adhesive coating steps, preferably, the waterborne polyurethane adhesive is an anionic waterborne polyurethane dispersion containing free carboxyl groups or free amino groups in its molecular chain segments, and the wet adhesive coating amount is controlled so that the dry adhesive weight is 12 g / m² to 15 g / m²; the surface drying treatment is carried out in a hot air environment at 45°C to 55°C; the lamination pressure during cold pressing is set to 0.5 MPa to 0.7 MPa, where the lamination pressure refers to the average pressure calculated based on the nominal projected area of ​​the pressure roller contact area. Within this range, the dry adhesive coating amount can provide sufficient chemical bonding sites. If it is below 12 g / m², insufficient adhesive and air bubbles are easily generated; if it is above 15 g / m², it will lead to cohesive failure of the adhesive layer and cause light scattering. The use of unheated cold pressing avoids the deformation of the micro-convex surface curvature of the surface grating caused by instantaneous high temperature, thus ensuring optical alignment. Furthermore, it is necessary to explain the colloidal stability of the adhesive on acid-pretreated paper: after pre-drying, there is no free liquid phase on the paper surface. The weak acid component is dispersed inside and outside the fiber in the form of microcrystals and adsorption. The measured pH value of the cold water extract of the pre-dried paper surface is 3.6. Combined with the steric stabilization mechanism of the above-mentioned anionic and nonionic composite stable dispersion, which is insensitive to pH value and electrolytes, no flocculation or demulsification was observed during the coating wetting and surface drying film formation processes. This is fundamentally different from the adhesion failure of the pre-crosslinking route described in the background art. The problem there is that the surface hydroxyl groups are consumed and blocked by the dense esterification network, and the strong acid remains at the service interface for a long time. In contrast, crosslinking has not yet occurred when the adhesive is applied in this invention. The hydroxyl groups on the fiber surface and the active ends of the coupling agent are completely preserved. The weak acid component will be consumed and incorporated into the network during thermal curing and will not remain at the interface.

[0012] According to one aspect of the present invention, in the low-temperature synergistic semi-interpenetrating network post-curing step, preferably, the working temperature of the first stage heat treatment is 90°C to 95°C, and the temperature is maintained for 10 to 20 minutes; the working temperature of the second stage heat treatment is 100°C to 110°C, the applied mechanical pressure is 0.05 MPa to 0.20 MPa, and the temperature is maintained for 20 to 30 minutes. In the first stage, at 90°C to 95°C, the residual trace moisture in the adhesive is forced to evaporate, the waterborne polyurethane macromolecular chains undergo strong physical entanglement, and the dehydration condensation reaction of the silanol groups and cellulose hydroxyl groups is fully deepened by acquiring a specific thermal history, expanding the small number of primary anchors formed in the pre-drying stage into a dense silicon-oxygen-carbon covalent anchoring layer. In the second stage, when the temperature rises to 100℃ to 110℃, dimethyl sulfone and the retained bound water synergistically plasticize the amorphous region of cellulose. Dynamic mechanical analysis shows that the segment relaxation peak of the amorphous region of the pre-impregnated paper sample shifts from around 138℃ in the parallel sample without dimethyl sulfone to around 103℃. The hydroxyl groups are released from hydrogen bond lock and restore nucleophilic activity and accessibility. This invention does not change the intrinsic energy barrier of the intramolecular ring-closing dehydration step of 1,2,3,4-butanetetracarboxylic acid, but removes the real rate-limiting matrix migration bottleneck at low temperatures. Combined with the nucleophilic catalysis of acyl transfer by sodium hypophosphite intermediate via acyl hypophosphite, the esterification crosslinking that originally required above 160℃ to be effectively advanced is completed within a 105℃ window. The measured apparent activation energy is reduced from 118 kJ / mol in the system without dimethyl sulfone to 68 kJ / mol. At this extremely low temperature, 1,2,3,4-butanetetracarboxylic acid generates an active cyclic anhydride and forms a rigid three-dimensional esterification network with cellulose; simultaneously, polyglycerol polyglycidyl ether undergoes ring-opening etherification and inserts into the network; and the organic epoxy end of the epoxy silane is forced to open, undergoing covalent addition with the free carboxyl or amino groups in the waterborne polyurethane. During the second stage of pressure holding, a release layer and a flexible pressure equalizing buffer pad are sequentially applied to the lens surface outside the cylindrical grating. The pressure holding load is uniformly distributed and transferred in the form of approximately hydrostatic pressure after the buffer pad elastically conforms to the curved surface of the lens. The mechanical holding pressure is controlled between 0.05 MPa and 0.20 MPa, which can not only overcome the interfacial layer expansion and delamination that may be caused by the volatilization of small molecules and provide the microscopic contact surface necessary for chemical bonding, but also has a modulus of more than one order of magnitude lower than that of the high-elasticity plateau modulus of the high-elasticity grating material at the same temperature, which is in the megapascal range; and the second temperature is only 20°C to 40°C higher than the glass transition temperature of the grating material, so the material is still in the high-elasticity plateau region, and the macroscopic zero-shear viscosity is still about seven orders of magnitude higher than that of the melt-processed state. The creep deformation driven by the residual small deviatoric stress after hydrostatic pressing is suppressed to within 1% of the lens sagitta height within 20 to 30 minutes, ensuring the integrity of the microstructure.

[0013] More preferably, the first temperature of the first stage heat treatment is constant at 95°C, the second temperature of the second stage heat treatment is constant at 105°C, and the mechanical holding pressure is constant at 0.10 MPa. Setting the second temperature to 105°C achieves a good balance between sufficient crosslinking conversion and no thermal damage to the grating. If the temperature is below 100°C, the esterification and ring-opening reaction rates are too low, and the reaction time is too long; if it is above 110°C, it approaches the thermal deformation critical point of the thermoplastic grating lens, which can easily induce optical aberrations.

[0014] Preferably, the paper substrate is selected from coated white cardboard or offset paper with a basis weight of 150 g / m² to 250 g / m²; the cylindrical lens grating is extruded from polyethylene terephthalate or modified polyethylene terephthalate, with an optical pitch of 40 LPI to 100 LPI, a material thickness of 0.35 mm to 0.90 mm, a refractive index greater than 1.5, and the material thickness t and the radius of curvature R and refractive index n of the cylindrical lens satisfy the focal length matching relationship t = nR / (n-1), with a deviation not exceeding ±8%. The geometric prerequisite for clear imaging with a cylindrical lens grating is that the underlying staggered image is located near the inner focal plane of the lens material. The depth of this focal plane, measured from the lens apex, is approximately nR / (n-1). Furthermore, the continuous arrangement of adjacent lenses requires a radius of curvature no less than half the pitch. Therefore, the thickness and pitch cannot be independently determined. Based on the above relationship, the matching thickness for 100 LPI is approximately 0.35 mm, and for 40 LPI, it is approximately 0.87 mm. This invention constrains both by the focal length matching relationship, ensuring that any combination within the scope of the claims possesses clear stereoscopic and flip imaging capabilities. This substrate combination ensures the load-bearing strength and stereoscopic optical transmittance of the final product.

[0015] More preferably, after completing the low-temperature synergistic semi-interpenetrating network thermal curing treatment, the paper-plastic structure is moved into a cooling chamber and gradually cooled to room temperature at a constant cooling rate for thermomechanical stress relaxation. Subsequently, it undergoes aging treatment in a constant temperature and humidity warehouse environment with a relative humidity of 50% and a temperature of 25°C. Gradient annealing and slow cooling can smoothly release the residual interlaminar thermomechanical shear stress generated when the heterogeneous composite material shrinks rapidly after heating, while the aging process under specific temperature and humidity conditions gradually stabilizes the conformation of the polymer chain segments, reducing internal stress rebound and latent warping during subsequent use.

[0016] Compared with the prior art, the present invention has the following beneficial effects: First, this invention alleviates the conflict between the high-temperature conditions required for crosslinking modification of paper-based fibers and the thermosensitive properties of grating lens materials. The synergistic effect of dimethyl sulfone as a hydrogen bond disruptor and sodium hypophosphite as a dehydration catalyst significantly reduces the apparent activation energy of the polycarboxylic acid crosslinking reaction, lowering the trigger temperature for deep esterification crosslinking to the range of 95°C to 105°C. Simultaneously, the release layer and flexible pressure-equalizing buffer pad applied to the lens surface transfer the pressure-holding load to the curved surface of the lens in an approximate hydrostatic pressure manner, thus suppressing both thermal and mechanical damage drivers. Therefore, the refractive microstructure of the cylindrical grating does not undergo thermal collapse or melting deformation throughout the post-stabilization process, maintaining micron-level optical alignment accuracy, and effectively controlling paper warping under temperature and humidity changes, as well as the resulting optical ghosting and aberrations.

[0017] Secondly, the multiphase bonding interface formed by the coexistence of a rigid crosslinked network and flexible polyether segments in this invention improves the paper-based embrittlement and interlayer delamination problems caused by traditional high-temperature crosslinking. During the low-temperature hot-pressing stage, the epoxy groups of polyglycerol polyglycidyl ether undergo ring-opening etherification with cellulose, and its long-chain polyether backbone is embedded in the crosslinked network, compensating for the loss of toughness in the matrix due to rigid crosslinking. The silanol end of the pre-hydrolyzed epoxy silane coupling agent covalently condenses with cellulose, and its epoxy end undergoes ring-opening addition with the waterborne polyurethane film, linking the paper base, coupling agent, and film into the same network. Thus, the interlayer bonding changes from primarily relying on physical adsorption to chemical covalent anchoring, significantly improving peel strength. During peeling, the failure surface shifts into the interior of the paper base, correspondingly improving the weather resistance and tear resistance of the product. Simultaneously, the low-temperature treatment avoids the thermal degradation of cellulose at high temperatures, maintaining the whiteness of the paper base. Attached Figure Description

[0018] Figure 1 This is a process flow diagram of one embodiment of the paper-based cylindrical lens grating printing thermal stabilization treatment method of the present invention; Figure 2 This is a cross-sectional schematic diagram of the stacked force transmission structure during the second stage of hot pressing and curing in step S4 of the present invention. Figure 3 This is a schematic diagram of the geometric optical path for the focal length matching relationship of the cylindrical lens grating in this invention.

[0019] In the figure: 1—Hot pressing platform; 2—Paper substrate; 3—Interlaced micro-image layer; 4—Waterborne polyurethane adhesive layer; 5—Cylinder grating sheet; 51—Lens surface of the cylinder grating sheet; 6—Release layer; 7—Flexible pressure equalization buffer pad; 8—Upper pressure plate; p—Grate pitch; R—Radius of curvature of the cylindrical lens; t—Thickness of the cylinder grating sheet material; F—Inner focal plane of the cylinder grating sheet material. Detailed Implementation

[0020] To make the objectives, technical solutions, and technical effects of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the embodiments described herein are only for explaining the invention and are not intended to limit the scope of protection of the invention. All equivalent substitutions and conventional changes made within the scope of the invention should fall within the scope defined by the claims. The order of operations in the following embodiments and comparative examples corresponds to steps S1 to S5 as described in the claims, wherein step S5 is an optional post-processing step. The overall process flow of the processing method of this invention is as follows: Figure 1 As shown.

[0021] The processing method provided by this invention is chemically designed around three parallel reaction pathways, all sharing the same low-temperature thermodynamic window. Firstly, 1,2,3,4-butanetetracarboxylic acid, under heating conditions, loses a water molecule between adjacent carboxyl groups within the molecule, closing to form a five-membered cyclic anhydride. The carbonyl carbon of this anhydride, under the action of a phosphorus-based nucleophilic catalytic center provided by sodium hypophosphite, accepts nucleophilic attack from the primary hydroxyl group with the least steric hindrance on the anhydrous glucose unit of cellulose, thus opening the ring to form an ester. This process repeats, establishing multiple ester bonds between adjacent cellulose molecular chains, thus binding the loose fiber bundles into a three-dimensional rigid network. In conventional dry-baking systems, the reason this reaction sequence requires temperatures above 160°C to proceed effectively is not due to the intrinsic chemical energy barrier of ring-closing dehydration, but rather because the amorphous regions of the dried paper are in a glassy frozen state, and the hydroxyl groups are locked by a hydrogen bond network, making it difficult for the anhydride to contact the nucleophilically active hydroxyl groups even if it is formed. This invention utilizes the highly polarized sulfone oxygen in the dimethyl sulfone molecule as a hydrogen bond acceptor, allowing it to penetrate into the amorphous region of cellulose during the pre-drying stage. It synergistically plasticizes with the retained bound water, compressing the relaxation window of the amorphous region into the 100°C to 110°C range. This competitively breaks the intramolecular and intermolecular hydrogen bond associations of cellulose, expanding the free volume between chain segments. This restores the nucleophilic activity and accessibility of hydroxyl groups and reduces the steric hindrance of crosslinking agents diffusing into the matrix, thus enabling deep esterification to be completed at around 105°C. Secondly, the multiple terminal epoxy groups of polyglycerol polyglycidyl ether maintain kinetic survival in a slightly acidic aqueous phase at room temperature by means of the subsequent feeding sequence and the limited shelf life. After the free water is removed by the sub-activated pre-drying, the acid-catalyzed hydrolysis terminates spontaneously due to the loss of the reaction medium, and the epoxy groups remain in the semi-dry matrix in a chemically sealed state. When the temperature is raised in the second stage, the epoxy groups open the ring nearby under the activation of the residual protic acid sites in the matrix. Part of them undergo ring-opening etherification with the cellulose hydroxyl groups that are not occupied by esterification, and another part adds to the dangling carboxyl groups of 1,2,3,4-butanetetracarboxylic acid to form esters. The terminal vicinal diols generated by the small amount of hydrolysis in the solution preparation and drying stages are also esterified by cyclic anhydrides and incorporated into the network in the same stage. The long and flexible polyether backbone is thus embedded between the rigid network by chemical bonds, undertaking the function of absorbing and dissipating heat and mechanical stress. Third, the pre-hydrolyzed epoxy silane coupling agent undergoes dehydration condensation with the hydroxyl groups on the surface of cellulose through the silanol end, generating a stable silicon-oxygen-carbon covalent bond that anchors it to the paper surface. Its outward-extending epoxy end opens the ring during the heating stage and undergoes covalent addition with the free carboxyl or amino groups reserved on the macromolecular chain of the waterborne polyurethane adhesive, thus chemically linking the paper base, coupling agent, and adhesive film together.It should be noted that the interlaced micro-images are printed using a halftone method, with the images and text composed of discrete dots. The intervals between sequential stripes, highlight areas, and non-image areas retain a large amount of uninked bare fiber surface. After the adhesive is applied, it directly wets and anchors the pre-treated fibers with coupling agents through these areas. This creates a high-density discrete dot matrix of interfacial covalent anchor points across the entire surface. The areas covered by the cured ink film are then bonded by the adhesive's wetting, spreading, and diffusion. The peeling crack front is pinned and deflected at these discrete anchor points, macroscopically manifesting as the damage surface extending into the paper matrix. The superposition of these three pathways results in the formation of a semi-interpenetrating network within the paper matrix, where rigid cross-links and flexible segments coexist, and covalent bonds are formed at the paper-plastic interface.

[0022] At the level of thermal-mechanical coupling, this method preserves the microstructure of the cylindrical lens grating based on verifiable quantitative constraints. Firstly, the second-stage temperature exceeds the glass transition temperature of the grating material by 20°C to 40°C. Considering the grating material used in Example 1 (with a glass transition temperature of 78°C measured by differential scanning calorimetry) operating at 105°C, the temperature is approximately 27°C. The material is in a high-elasticity plateau region and far from entering a processable flow state. Its macroscopic zero-shear viscosity, anchored to the material's typical extrusion viscosity of 10³ Pa·s at 240°C, and extrapolated using the WLF equation with universal constants, is approximately 10¹ Pa·s at 105°C. 0 The viscosity is on the order of Pa·s. The chain entanglement amplification factor (the ratio of weight-average molecular weight to entanglement molecular weight, approximately 10¹² Pa·s in this material) is multiplied by the conventional value of the segmental viscosity at the glass transition (10¹² Pa·s). 4 The bottom-up estimation yields terminal flow viscosity values ​​of the same order of magnitude, with the two independent paths corroborating each other. If the conventional value of chain segment viscosity is mistakenly extrapolated without considering entanglement contributions, a value approximately four orders of magnitude lower will be obtained. However, this corresponds to local relaxation of the chain segment, not the terminal behavior of macroscopic lens flow. Secondly, the nominal holding pressure of 0.05 MPa to 0.20 MPa is more than an order of magnitude lower than the high elastic plateau modulus of the grating material at that temperature, which is in the megapascal range. The resulting elastic compressive strain is on the order of a few percent and immediately recovers to a high elastic state upon decompression, thus permanent deformation is not considered. Third, the lens array is a continuous corrugated layer with interconnected ridges and valleys. The ratio of the arc height to the pitch is approximately one-tenth. Under the close coverage of the release layer and the flexible pressure-equalizing buffer pad, the contact pressure acts approximately uniformly along the normal direction on the entire curved surface. Laterally, it is constrained by adjacent units, and the stress state is close to lateral compression. The deviatoric stress component that actually drives the shape change is only on the order of one-tenth of the nominal pressure, i.e., about 0.01 MPa to 0.02 MPa, according to the geometry of this shallow arc. Based on this, the permanent creep strain is estimated with a deviatoric stress of 0.01 MPa, a holding time of 1500 seconds, and a viscosity of 10. 9 Pa·s to 10¹ 0In the Pa·s range, an envelope of 0.15% to 1.5% is obtained by multiplying stress by time and then dividing by viscosity. The measured sagittal height change rate of 0.3% to 0.8% in each embodiment falls within this range, and the source of each input quantity used in the estimation is given above or in the test method. In contrast, at a conventional baking temperature of 170°C, the viscosity drops to 10% according to the same WLF relationship. 5 At Pa·s levels, approximately five orders of magnitude lower than 105℃, creep deformation under the same load and time is magnified by a factor of 100,000, making lens collapse inevitable. The low-temperature window defines the lower limit of viscosity, and the equalization buffer defines the upper limit of deviatoric stress. Together, they constitute sufficient conditions for the non-destructive nature of optical microstructures. For experimental definitions, please refer to Comparative Examples 4 and 5.

[0023] Unless otherwise specified, the raw materials used in the following examples and comparative examples are as follows: 1,2,3,4-Butanetetracarboxylic acid is a white crystalline powder with a purity of not less than 99.5% and a moisture content of not more than 0.5%; sodium hypophosphite monohydrate is analytical grade with a purity of not less than 99.0% and a transition metal ion content of not more than 10 parts per million; dimethyl sulfone has a purity of not less than 99.0%; the multifunctional water-soluble epoxy resin is polyglycerol polyglycidyl ether with an aliphatic skeleton, grade EX-512, with not less than 4 epoxy groups, an epoxy equivalent of approximately 168 g / eq, a viscosity of approximately 1300 mPa·s at 25°C, a total chlorine content of not more than 6.5%, and is miscible with water in any proportion; the epoxy silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a purity of not less than 98.0%; the waterborne polyurethane adhesive is a single-component anionic type. The aqueous polyurethane dispersion has a solids content of 40% ± 2%. Its molecular chain contains incompletely neutralized free carboxyl groups introduced by a dimethylolpropionic acid-based hydrophilic chain extender. It forms a transparent film with near-zero volatile organic compound content. In addition to the carboxylic acid-type internal emulsification, it is grafted with nonionic hydrophilic polyethylene oxide side chains, making it an anionic and nonionic composite stable type. The volume average particle size is approximately 60 nm. Stability testing showed no flocculation or stratification after 24 hours in a pH 3.0 buffer solution and a 0.1 mol / L calcium chloride solution. The paper substrate is commercially available coated white cardboard or offset paper with a basis weight between 150 g / m² and 250 g / m², specific specifications are detailed in the examples. The cylindrical grating is extruded from polyethylene terephthalate or modified polyethylene terephthalate, with a refractive index greater than 1.5; pitch and thickness are detailed in the examples. The water used for solution preparation and hydrolysis is deionized water with a conductivity not exceeding 10 μS / cm.

[0024] The pre-hydrolyzed epoxy silane coupling agents in each example were prepared as follows: 120 parts by weight were taken from 1000 parts by weight of deionized water in the total formulation and placed in a polyethylene container equipped with a dispersing stirrer. The pH was adjusted to 4.0 with glacial acetic acid. The mixture was stirred at approximately 150 rpm at 25°C while a measured amount of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was slowly added dropwise. After the addition was complete, stirring and hydrolysis continued for 30 to 45 minutes. The hydrolysate was obtained when the liquid changed from an initial slightly turbid state to a completely transparent homogeneous solution. It was prepared and used immediately. A pH of 4.0 falls within the kinetic window where the methoxy group hydrolysis rate is relatively fast while the silanol self-condensation rate is relatively slow, which allows for more complete hydrolysis and inhibits the formation of ineffective silica gels.

[0025] The performance of each sample was determined according to the following method. Unless otherwise specified, before testing, all samples were equilibrated for 24 hours under standard atmospheric conditions of 23℃±1℃ and 50%±2% relative humidity, as specified in GB / T 10739—2023 "Standard Atmospheric Conditions for the Treatment and Testing of Paper, Paperboard and Pulp Samples". The arithmetic mean of 5 parallel samples was taken for each index, and the test results were rounded according to the rules of GB / T 8170—2008. The conductivity of the deionized water used for solution preparation, hydrolysis and various tests was determined according to the method specified in GB / T 6682—2008, and the measured value was not higher than 10 μS / cm.

[0026] Raw materials and process parameters were characterized as follows. The basis weight of the paper substrate was determined according to GB / T 451.2—2023. The moisture content of the paper substrate was monitored using an online microwave moisture meter and periodically checked according to the oven drying method specified in GB / T 462—2023. The absolute moisture content refers to the percentage ratio of the mass of water in the sample to its oven-dried mass after drying to constant weight at 105℃±2℃. For the sizing tape liquid rate, a 100mm×100mm wet paper sample was randomly cut from the sizing roll exit. The wet weight was immediately measured using a balance with an accuracy of 0.001g. The sample was then dried to constant weight using the oven drying method of GB / T 462—2023 and the dry weight was measured. The dry weight was expressed as the percentage of the difference between the wet and dry weights divided by the dry weight, and the arithmetic mean of three samples was taken. The dry adhesive weight is calculated by dividing the difference in mass of the same sample before and after coating under the above-mentioned standard atmospheric conditions by the coating area. It is then checked against the wet adhesive tank reduction and the converted value of the non-volatile matter content of the adhesive measured according to GB / T 2793—1995. If the deviation between the two is no more than 5%, the gravimetric method result is adopted. The pH value of the cold water extract of the pre-dried paper surface is determined according to the pH meter method specified in GB / T 1545—2008. After the sample is cut into small pieces, it is extracted in deionized water at 23℃±1℃ for 1 hour at a solid-liquid ratio of 1:20 before the pH value is read. The solids content of the adhesive was determined according to GB / T 2793—1995; the viscosity of the adhesive and polyglycerol polyglycidyl ether was determined according to the single-cylinder rotational viscometer method specified in GB / T 2794—2022 at 25℃±0.5℃; the volume average particle size of the adhesive was determined by a laser particle size analyzer according to the principle of dynamic light scattering at 25℃±0.5℃; the epoxy equivalent of polyglycerol polyglycidyl ether was determined according to GB / T 4612. The Shore A hardness of the flexible pressure equalizing buffer pad was determined according to GB / T 531.1—2008. The refractive index of the cylindrical grating was measured using an Abbe refractometer at 23℃±1℃ under sodium D line; its optical pitch was obtained by dividing the total span of the ridge centers of 20 consecutive lens units by 20 using a measurement microscope with charge-coupled device imaging, and then converting it to a pitch in micrometers based on the line count per inch being equal to 25400; its glass transition temperature was determined by differential scanning calorimetry as specified in GB / T 19466.2—2004, with a sample mass of 5mg to 10mg, under nitrogen atmosphere, at a heating rate of 10℃ / min, and read from the midpoint temperature.

[0027] The properties of the finished product were determined according to the following method. The dimensional change rate under damp heat was tested according to the Cab constant damp heat test method specified in GB / T 2423.3—2016. The severity level was set at a temperature of 85℃, a relative humidity of 85%, and an exposure time of 72 hours. A 100mm × 100mm finished product sample marked with a 100mm gauge length crosshair was placed in the test chamber for continuous exposure. After removal, the sample was re-equilibrated under the above standard atmospheric conditions for 24 hours. The gauge length was then re-measured at the same location using a two-dimensional image measuring instrument. The larger of the absolute values ​​of the longitudinal and transverse dimensional change rates was reported. Optical alignment accuracy drift was measured twice, before and after the same damp heat aging test. A measurement microscope with charge-coupled device imaging was used, with an objective magnification of not less than 100x and a length resolution of not less than 0.5μm. Two measurement points, 25.4mm apart, were selected along the grating arrangement direction. The lateral displacement between the center of the cylindrical lens ridge and the center of the reference grating of the underlying interlaced pattern was read. The difference between the two was the cumulative phase displacement within the reference segment. The number of lens units in the segment was obtained by dividing the length of the segment by the pitch of the reference grating of the underlying interlaced pattern. The difference between the lens pitch and the pattern pitch was obtained by dividing the cumulative phase displacement by the number of lens units. Then, the number of lines per inch was calculated by dividing 25400 by the pitch in micrometers, and the absolute value of the difference was taken as the pitch offset measured in this test. The absolute value of the difference between the two pitch offsets before and after aging was the alignment drift after aging, expressed in lines per inch. Meanwhile, an observer, positioned 300mm away from the sample under a D65 standard light source, with the viewing angle oscillating within a 45° range on either side of the normal, visually evaluates whether there is ghosting or weakened depth of field in the stereo and flip images. The interlayer peel strength test was conducted according to the principles and procedures specified in GB / T 2790—1995 "Test Method for 180° Peel Strength of Adhesives - Flexible Materials vs. Rigid Materials". In this invention, the cylindrical lens grating sheet is the rigid adherend, and the paper substrate is the flexible adherend. The sample is 15 mm wide and 200 mm long, with 50 mm pre-peeled along the length direction. The end of the grating sheet is fixed to the rigid clamping stage, and the end of the paper substrate is clamped to the upper clamp. Peeling is performed along the 180° direction at a rate of 200 mm / min, with a peel length of not less than 100 mm. The average value of the steady-state segment after removing the first and last 20 mm of the peel force-displacement curve is taken, and the result is expressed as N / 15 mm. The above sample width and peeling rate were uniformly selected to adapt to the cutting specifications and range of the product of this invention. All examples and comparative examples were measured under exactly the same conditions, and the data obtained are comparable to each other. After peeling, the damaged surface was observed with a stereomicroscope and the damage type was determined according to the following criteria: if the damaged surface is located inside the paper base and obvious fiber pull-out and tearing are visible, it is judged as cohesive damage of the paper base; if the damaged surface is located inside the paper base but is flat and brittle without fiber pull-out, it is judged as brittle delamination of the paper base; if the damaged surface is located between the adhesive layer and the paper surface and the paper surface is basically intact, it is judged as adhesive-paper interface peeling; if two or more morphologies coexist on the same sample and each accounts for no less than 30%, it is judged as mixed damage.Considering that the composite finished product cannot be directly tested for tearing and whiteness, parallel paper samples were prepared simultaneously for each case. These samples were unprinted, unlaminated, but underwent the same impregnation treatment and thermal history as the finished product. Tear strength was determined according to GB / T 455—2002 using the Ellimentoff method. The tear retention rate was expressed as a percentage of the tear strength of the parallel paper sample to the tear strength of the untreated base paper in the same batch. Both were calculated as the arithmetic mean of the longitudinal and transverse measurements. Whiteness was determined according to GB / T 22880—2008 under D65 light source and 10° field of view conditions. This standard was modified to adopt ISO 11475. The method for determining the warpage height was as follows: after the finished product sample underwent the above-mentioned damp heat aging and rebalancing, the concave side was placed freely flat on a marble platform with a flatness of not less than 0, without applying any external force. After standing for 30 minutes, the maximum value of the warpage at the four corners was measured with a feeler gauge, and the reading was accurate to 0.1 mm. The integrity of the cylindrical lens microstructure was characterized by measuring the relative change rate of the sagittal height of the lens unit before and after the entire heat curing process using laser confocal microscopy. The sagittal height was defined as the vertical distance from the vertex of a single lens unit to the line connecting the valleys on its adjacent sides. A permanent mark was made on the sample, and 10 consecutive lens units were measured at the same mark position before and after the treatment. The arithmetic mean was taken. A change rate of no more than 1% was considered to be intact.

[0028] The reaction process and structural evolution involved in this invention were characterized by the following method. The qualitative criterion for the degree of esterification crosslinking was attenuated total reflectance infrared spectroscopy, according to the general rules of GB / T 6040—2019, with a diamond attenuated total reflectance attachment, a scanning range of 4000 cm⁻¹ to 650 cm⁻¹, a resolution of 4 cm⁻¹, and 32 cumulative scans. The sample was first rinsed with 0.1% sodium carbonate solution and dried to convert the residual free carboxylic acid into carboxylate and eliminate its carbonyl absorption interference. The relative strength of the characteristic absorption of ester carbonyl near 1728 cm⁻¹ was observed, and the presence and consumption of epoxy groups were judged by the characteristic absorption of epoxy near 910 cm⁻¹. The cyclic anhydride intermediate was tracked using in-situ temperature-dependent attenuation total reflectance infrared spectroscopy with a temperature-controlled accessory. The sample was heated from 90℃ to 105℃ at a rate of 1℃ / min and then held at that temperature. Spectra were acquired every 2 minutes, and the rise and fall of the characteristic double peaks at 1849 cm⁻¹ and 1779 cm⁻¹ were observed. The epoxy value in the working solution and pre-dried paper samples was determined according to Method A of GB / T 1677—2023, i.e., the hydrochloric acid-acetone method. The epoxy retention rate was expressed as the percentage of the measured epoxy value to the initial theoretical epoxy value calculated based on the input. Before the paper sample was measured, it was rapidly extracted with deionized water at 4℃ at a solid-liquid ratio of 1:50 for 3 minutes and then immediately filtered. The degree of esterification was quantified using saponification titration combined with an infrared internal standard method. Samples washed and dried with dilute sodium carbonate solution were refluxed in a 0.5 mol / L sodium hydroxide-ethanol solution for 2 hours for saponification. Excess alkali was then back-titrated with a standard hydrochloric acid solution. Simultaneously, the carbon-oxygen stretching vibration absorption of cellulose near 1030 cm⁻¹ was used as an internal standard. The ratio of absorbance at 1728 cm⁻¹ to the absorbance of the internal standard peak was used for relative quantification. The results of the two methods were cross-validated, and the amount of ester bonds at the plateau value was normalized to 100%. The apparent activation energy was determined by sampling five points at 95℃, 100℃, 105℃, and 110℃ for five different incubation times, measuring the degree of esterification, and plotting conversion-time curves. The slope of the initial segment of the curve at each temperature was used as the initial rate. A linear fit was performed on the logarithm of the initial rate and the reciprocal of the temperature according to the Arrhenius equation, and the initial rate was obtained from the slope. The chain segment relaxation temperature of the amorphous region of the pre-impregnated paper sample was determined according to GB / T 33061.1—2025, using a dynamic mechanical analyzer under a thin film stretching fixture at a frequency of 1 Hz, a heating rate of 3 ℃ / min, and a temperature range of 40 ℃ to 180 ℃, based on the peak position of the loss factor. Total silicon and hot water extractable silicon were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). Total silicon was measured after microwave digestion of the sample with nitric acid and hydrofluoric acid. Hot water extractable silicon was measured after extraction with 95 ℃ deionized water at a solid-liquid ratio of 1:50 for 1 hour, followed by filtration and determination of the filtrate. The average ink film coverage of the interlaced image was determined by acquiring the image and text using a platform scanner in 600 dpi, 8-bit grayscale mode. The threshold was determined using the maximum inter-class variance method for binarization analysis, and the result was expressed as the percentage of inked pixels to total pixels, with the arithmetic mean of five different regions taken.

[0029] Example 1 Prepare the pre-impregnated stabilizing solution as follows: Inject 880 parts by mass of deionized water into a jacketed reactor lined with an anti-corrosion coating. Turn on the circulating water bath to raise the water temperature to 35°C to 40°C. Add 65 parts by mass of 1,2,3,4-butanetetracarboxylic acid while stirring at approximately 300 rpm. Continue stirring for approximately 30 minutes until the powder is completely dissolved, obtaining a clear mother liquor. The measured pH value at this point is approximately 2.0. Cool the jacket with cooling water to lower the temperature of the solution to 25°C ± 2°C and maintain this temperature throughout the subsequent solution preparation process. Slowly add 15 parts by mass of dimethyl sulfone and 45 parts by mass of sodium hypophosphite monohydrate sequentially. After the addition is complete, continue homogenization for 15 minutes. A 30% sodium hydroxide solution was slowly added dropwise using a titration pump, with real-time monitoring via an online pH meter. Approximately 9 parts by mass were added in total to pre-adjust the pH of the system to around 3.0. The amount of water introduced by the concentrated alkali adjustment was less than one percent of the aqueous phase reference, and had no substantial impact on the component ratios based on 1000 parts by mass of aqueous medium. This step was scheduled to be completed before the addition of the epoxy-containing component to avoid unnecessary hydrolysis loss of epoxy groups in the strongly acidic mother liquor with a pH of around 2.0. Subsequently, 25 parts by weight of polyglycerol polyglycidyl ether were added to a constant-pressure dropping funnel and added dropwise over 10 to 12 minutes at a uniform rate to avoid excessive local epoxy concentration that could induce microgelation. Then, the hydrolysate of the epoxy-based silane coupling agent prepared according to the aforementioned general method was poured in. This hydrolysate contained 120 parts by weight of deionized water, equivalent to 12 parts by weight of effective pure γ-(2,3-epoxypropoxy)propyltrimethoxysilane. After stirring and homogenizing for another 5 minutes, the pH was retested and found to be 3.02. The solution was then filtered online through a 200-mesh screen to obtain a slightly yellow, transparent pre-impregnated stabilized solution free of any suspended matter. The epoxy retention rate of this working solution was monitored using the hydrochloric acid-acetone method. Immediately after preparation, at 2 hours, and at 4 hours, the retention rates were 97.8%, 93.6%, and 88.4%, respectively. After 8 hours, the retention rate decreased to 75.9%. Based on this, the working solution was limited to a usable period of 4 hours after preparation; in this example, it was used within 2 hours.

[0030] Coated white cardboard with a basis weight of 200 g / m² was cut into 650 mm × 950 mm samples. Each sample was passed individually through a shallow glue tank containing the aforementioned stabilizing solution on an experimental two-roll press sizing device. The linear pressure of the sizing rollers was adjusted to stabilize the liquid content between 75% and 80%. In this example, the measured liquid content was 77.6%. The wet paper samples after liquid removal were then flattened and fed into a two-stage drying oven combining infrared preheating and forced hot air circulation. The first stage was at 60°C for 3 minutes, and the second stage was at 80°C for 2 minutes. The majority of the free water was removed within one to two minutes of entering the first stage. After exiting the oven, the absolute moisture content of the paper base was measured using a microwave moisture meter and verified by the oven drying method. The result was 4.8%. The pre-dried paper sample was rapidly extracted with deionized water at 4°C and the epoxy retention rate was calculated using the hydrochloric acid-acetone method. The epoxy retention rate was 82.7%. The infrared difference spectrum of the paper and the untreated base paper from the same batch showed clear epoxy characteristic absorption near 910 cm⁻¹, indicating that the epoxy-containing component was chemically sealed and retained for subsequent processes. In continuous production, a multi-layer reciprocating hot air drying tunnel can be configured after the roll-to-roll sizing machine. The residence time for the two stages is matched according to the machine speed and the effective travel length of the drying tunnel. For example, a machine speed of 8 m / min corresponds to an effective airflow of 24 m for the first stage and 16 m for the second stage. The drying endpoint is controlled in a closed loop using an online microwave moisture meter at an absolute moisture content of 4.0% to 5.5%. In this example, subsequent printing, lamination, and curing were all performed using sample sheets. The paper pre-dried using this sub-activation method was smooth and flexible, with no surface crystallization. Printability testing showed that its ink absorbency was comparable to that of the untreated base paper.

[0031] An interlaced micro-image sequence, generated by a raster image algorithm with a 75 LPI pitch, was printed on pre-treated paper using high-precision UV-cured offset printing. After instantaneous UV curing, the image edges were clear and free of bleeding. Binarization analysis of the scanned images showed that the average ink film coverage of the interlaced images in this example was 54.8%, and the uninked bare fiber areas remained connected between the intervals of the sequence strips and the highlight areas. The aforementioned anionic aqueous polyurethane dispersion was uniformly coated onto the printing surface using a ceramic anilox roller. The wet adhesive amount was controlled to achieve a dry adhesive amount of 13.5 g / m², followed by surface drying in a hot air tunnel at 50°C and a wind speed of 1.5 m / s for approximately 1 minute. The adhesive layer exhibited a slightly viscoelastic state with a touch-dry texture. A polyethylene terephthalate cylindrical grating sheet 5 with a pitch of 75 LPI, a thickness of 0.47 mm, and a refractive index of 1.57 was used, with a lens curvature radius of 0.172 mm. Figure 3As shown, the radius of curvature R of the cylindrical lens, the material thickness t, and the refractive index n satisfy the focal length matching relationship t=nR / (n-1), so that the interlaced micro-image layer 3 is located at the inner focal plane F of the material. The lens texture line and the interlaced image line of the bottom layer are aligned with the machine vision and charge-coupled device camera tracking system, and the phase deviation is controlled within ±5μm. The composite is cold-pressed by a pair of room temperature rubber laminating rollers at a lamination pressure of 0.6MPa (calculated according to the nominal projected area of ​​the roller contact area, the same below), without heating throughout the process. After lamination, there are no residual air bubbles visible to the naked eye, resulting in a paper-plastic structure.

[0032] The paper-plastic structure is smoothly fed into a flat-plate hot press with proportional-integral-derivative temperature control, and its layered force transmission structure is as follows: Figure 2 As shown, from bottom to top, the components are: a hot pressing platform 1, a paper substrate 2, an interlaced micro-image layer 3, a water-based polyurethane adhesive layer 4, a cylindrical lens grating 5, a release layer 6, a flexible pressure equalizing buffer pad 7, and an upper pressure plate 8. The lens surface 51 of the cylindrical lens grating 5 faces upward and is pressured by the release layer 6. During operation, a 0.05mm thick polytetrafluoroethylene release cloth and a 3mm thick silicone rubber pressure equalizing buffer pad with a Shore A hardness of 50 are laid flat on the lens surface 51 in sequence, forming the release layer 6 and the flexible pressure equalizing buffer pad 7, respectively. The temperature is first kept constant at 95℃ for 15 minutes. During this stage, no additional pressure is applied, and the upper pressure plate is held together by the weight of the buffer pad. Then, the temperature is raised to 105℃ and a vertical holding pressure of 0.10MPa is applied simultaneously. The load is evenly distributed after the buffer pad elastically adheres to the curved surface of the lens, and the temperature is kept constant for 25 minutes. After being removed from the oven, the product is transferred to a slow cooling chamber and gradually cooled to room temperature at a constant cooling rate of 2℃ / min. It is then aged in a constant temperature and humidity warehouse at 25℃ and 50% relative humidity for 24 hours to obtain the finished product. The finished product has a flat surface, and the curved surface contour of the lens array is intact under a laser confocal microscope. The change rate of the arc height is 0.4%, and the stereoscopic and flip images are clear and sharp.

[0033] Example 2 This example examines the lower limit combination of the scope defined by the claims. The pre-impregnation stabilizing solution contained 60 parts by mass of 1,2,3,4-butanetetracarboxylic acid, 40 parts by mass of sodium hypophosphite monohydrate, 10 parts by mass of dimethyl sulfone, 20 parts by mass of polyglycerol polyglycidyl ether, and 10 parts by mass of epoxysilane coupling agent (calculated based on effective pure material). The pH of the system was adjusted to 2.8. The measured application rate was 75.3%, and the moisture content at the pre-drying endpoint was 5.4%. The dry adhesive weight was 12.1 g / m², the surface drying temperature was 45°C, and the cold pressing pressure was 0.5 MPa. The first stage of post-curing was a constant temperature of 90°C for 20 minutes, and the second stage was a constant temperature of 100°C at 0.05 MPa for 30 minutes. All other raw materials, equipment, and operations were the same as in Example 1.

[0034] Example 3 This example examines the upper limit combination. 70 parts by mass of 1,2,3,4-butanetetracarboxylic acid, 50 parts by mass of sodium hypophosphite monohydrate, 20 parts by mass of dimethyl sulfone, 30 parts by mass of polyglycerol polyglycidyl ether, and 15 parts by mass of epoxysilane coupling agent (equivalent to effective pure material). The pH was adjusted to 3.2; the measured liquid carryover rate was 79.5%, and the moisture content at the pre-drying endpoint was 4.1%; the dry adhesive weight was 14.8 g / m², the surface drying temperature was 55°C, and the cold pressing pressure was 0.7 MPa; the first stage was maintained at 95°C for 10 minutes, and the second stage was maintained at 110°C and 0.20 MPa for 20 minutes. The rest was the same as in Example 1.

[0035] Example 4 This example examines the compatibility between the substrate and the grating specifications. The paper substrate was replaced with 150 g / m² offset paper, and the cylindrical lens grating was replaced with a modified polyethylene terephthalate extruded grating with a pitch of 100 LPI, a thickness of 0.35 mm, and a refractive index of 1.56. Its lens radius of curvature was 0.127 mm, meeting the focal length matching requirement. The formulation and all process conditions were the same as in Example 1. This example was repeated using coated white cardboard with a basis weight of 250 g / m² and a polyethylene terephthalate grating with a pitch of 40 LPI, a thickness of 0.88 mm, and a lens radius of curvature of 0.320 mm. The performance of the obtained samples was at the same level as the data listed in Table 1, with no systematic differences observed.

[0036] Example 5 The only difference between this example and Example 1 is that the gradient cooling and aging treatment after heat curing is omitted. That is, after the sample is cured at 105°C under pressure and removed from the oven, it is placed directly in the workshop at room temperature for natural cooling. It does not enter the slow cooling chamber or undergo constant temperature and humidity aging. Everything else is the same as Example 1.

[0037] Example 6 The only difference between this example and Example 1 is that the second-stage heat treatment temperature is reduced from 105°C to 100°C, the isothermal time remains 25 minutes, and the holding pressure remains 0.10 MPa. All other aspects are the same as in Example 1, in order to investigate the effect of the curing temperature variation within the preferred window on the degree of crosslinking completion.

[0038] Comparative Example 1 The only difference between this example and Example 1 is that dimethyl sulfone is not added when preparing the pre-impregnation stabilizing solution; all other components, dosages, and process conditions are the same as in Example 1.

[0039] Comparative Example 2 The only difference between this example and Example 1 is that polyglycerol polyglycidyl ether is not added when preparing the pre-impregnation stabilizing solution; otherwise, they are the same as in Example 1.

[0040] Comparative Example 3 The only difference between this example and Example 1 is that no pre-hydrolyzed epoxy silane coupling agent is added when preparing the pre-impregnation stabilizing solution; otherwise, they are the same as in Example 1.

[0041] Comparative Example 4 This example simulates the conventional high-temperature crosslinking route of polycarboxylic acids in existing technologies. The impregnation solution consists only of 65 parts by weight of 1,2,3,4-butanetetracarboxylic acid and 45 parts by weight of sodium hypophosphite monohydrate dissolved in 1000 parts by weight of deionized water, without pH adjustment, and the measured value is approximately 2.1. The sizing, pre-drying, printing, coating, and cold pressing operations are the same as in Example 1. The post-heat treatment does not use the two-stage low-temperature process, but instead, under the same conditions as in Example 1, with a polytetrafluoroethylene release cloth and a silicone rubber pressure equalizing buffer pad, it is hot-pressed for 3 minutes at 170°C and 0.10 MPa according to conventional baking conditions. After exiting the oven, the surface of the cylindrical grating is visually observed to be completely fogged, the lens unit is softened and collapsed over a large area, the measured change rate of the sagittal height reaches 38.6%, the stereoscopic imaging is completely lost and accompanied by severe ghosting, the optical alignment drift can no longer be read using the established method, and the paper base is obviously yellowed. As a supplementary investigation, another set of samples was prepared in the order of cross-linking followed by lamination. That is, the base paper impregnated with the same formula was first baked at 170℃ for 90 seconds to complete the cross-linking, and then printed, coated with glue, and cold-pressed for lamination without further heat curing. Although the lens was preserved, the peel strength of the sample was only 6.8N / 15mm and it was an interfacial peel between the glue layer and the paper surface. The tear retention rate of the parallel paper sample was 54.7%, and the whiteness was 68.3. This indicates that the surface active site blockage, strong acid residue, and fiber embrittlement caused by high-temperature pre-cross-linking also cannot produce usable products.

[0042] Comparative Example 5 The only difference between this example and Example 1 is that in step S4, the PTFE release cloth and silicone rubber pressure equalizing buffer pad covering the lens surface are removed, allowing the polished metal upper pressure plate to directly contact the curved surface of the cylindrical lens grating in the second stage. The temperature, holding pressure, and holding time in both stages are the same as in Example 1, and everything else is also the same as in Example 1. After cooling from the furnace, periodic bright bands corresponding to the contact area of ​​the pressure plate can be visually observed on the plate surface. Under a laser confocal microscope, there is obvious local flattening and lateral flow at the tooth tips of the lens unit.

[0043] The above-described embodiments and comparative samples were tested using the aforementioned test methods, and the results are summarized in Table 1.

[0044] Table 1 Performance Test Results The data comparison in Table 1 clearly demonstrates the causal relationship and synergistic necessity among the various technical features of this invention. After continuous exposure at 85°C and 85% relative humidity for 72 hours, the dimensional change rate of Examples 1 to 6 did not exceed 0.11%, the optical alignment drift did not exceed 0.07 LPI, and visual observation revealed no ghosting in either stereoscopic or flipping effects. The peel strength was above 22 N / 15 mm, with damage occurring within the paper base; the tear retention rate remained stable above 92%; the whiteness remained above 82; and the lens sagittal height change rate was within 1%. This data simultaneously satisfies the inherently conflicting requirements of dimensional locking, interface anchoring, toughness preservation, and non-destructive optical microstructure, while each comparative example showed a precipitous deterioration in one or more of these indicators.

[0045] The results of Comparative Example 1 confirm the crucial role of dimethyl sulfone in low-temperature crosslinking. Without dimethyl sulfone, although sodium hypophosphite remained in place, esterification crosslinking at 105°C almost ceased. Infrared analysis showed that after rinsing with dilute sodium carbonate, the sample exhibited only a weak shoulder peak near 1728 cm⁻¹, while Example 1 showed a clear strong absorption at the same position for the ester carbonyl group. Even more discriminative was the in-situ temperature-varying infrared evidence: during the heating process from 90°C to 105°C, both systems showed characteristic double peaks of cyclic anhydrides at 1849 cm⁻¹ and 1779 cm⁻¹. In the Comparative Example 1 system, this double peak continued to accumulate while the ester peak hardly increased. In the Example 1 system, the double peak first rose and then fell back, showing a clear precursor-product relationship with the growth of the ester peak at 1728 cm⁻¹. This indicates that the hindered process at low temperatures is not the formation of cyclic anhydrides, but rather the nucleophilic attack of cellulose hydroxyl groups on the anhydrides. Without dimethyl sulfone, the amorphous region remains frozen, and the hydroxyl groups are still locked by hydrogen bonds, preventing the consumption of the generated anhydrides. Macroscopically, the sample exhibits a wet-heat dimensional change rate as high as 1.82%, approaching the approximately 2.4% level measured in the same batch of directly composite samples without any impregnation treatment. After aging, the warpage height reaches 3.6 mm, with a positional drift of 0.46 LPI, resulting in visible ghosting and a loss of stereoscopic depth in imaging. Interestingly, its tear resistance retention and whiteness are slightly higher than other examples, which conversely demonstrates that the cellulose in this sample is essentially not cross-linked, completely failing to achieve the dimensional stabilization target. The presence of dimethyl sulfone is indispensable for initiating deep esterification within the low-temperature window.

[0046] To validate the above attributions at the kinetic level, the temperature-dependent conversion rate-time curves of the intact system and the system without dimethyl sulfone were separately measured. The degree of esterification was quantified by saponification titration combined with infrared internal standard method. Samples were taken at 95℃, 100℃, 105℃, and 110℃ for five incubation periods. The degree of esterification of the intact system exhibited a first-order approximation characteristic with time, reaching over 90% of the plateau value at 105℃ after 25 minutes. The degree of esterification of the system without dimethyl sulfone, after 60 minutes of incubation at 110℃, was less than 10% of the plateau value of the intact system. Arrhenius fitting using the initial rate method showed that the apparent activation energy of the intact system was 68 kJ / mol, while that of the system without dimethyl sulfone was 118 kJ / mol. The initial rate of the former at 105℃ was approximately forty times that of the latter. It is important to emphasize that this difference in apparent activation energy does not mean that the intrinsic energy barrier of the intramolecular ring-closing step has been changed. It is a macroscopic projection of the rate-limiting step switching from matrix migration control to chemical reaction control, which is corroborated by the shift of the chain segment relaxation peak from 138℃ to 103℃ measured by dynamic mechanical analysis. Thus, the four independent types of evidence—temperature-dependent conversion curve, apparent activation energy, anhydride intermediate fluctuations, and matrix relaxation peak position—are closed, clearly attributing the macroscopic difference in Comparative Example 1 to the removal of the migration bottleneck.

[0047] Comparative Example 2 demonstrates that a single rigid crosslinked network lacks engineering usability. Without the flexible polyether segments of polyglycerol polyglycidyl ether, the dense ester network constructed from 1,2,3,4-butanetetracarboxylic acid completely compresses the slip freedom of the cellulose segments, leaving no outlet for internal stress. The tear strength retention rate of the parallel paper sample plummets to 56.4%, and in the peel test, the failure mode transforms into brittle delamination of the paper base, with the peel strength dropping to 15.7 N / 15 mm. After damp heat aging, local pattern misalignment caused by microcrack propagation further increases the alignment drift to 0.11 LPI. In contrast, in the various embodiments, the flexible polyether segments are chemically embedded in the network through both ring-opening etherification and pendant carboxyl addition, dispersing between the rigid framework to act as a stress buffer, resulting in a tear strength retention rate exceeding 92%. This illustrates the necessity of using a structure design that combines a rigid network with flexible segments.

[0048] Comparative Example 3 reveals the decisive role of interfacial covalent bridging in service reliability. Without the pre-hydrolyzed epoxy silane coupling agent, the paper-adhesive interface relies solely on physical adsorption such as hydrogen bonds and van der Waals forces. The initial peel strength is only 7.4 N / 15 mm, exhibiting interfacial peeling. During hygrothermal aging, polar water molecules penetrate along the interface, causing fine bubbling at the sample edges and leading to localized floating of the lens array, with a displacement of 0.21 LPI. In the examples containing the coupling agent, the silicon-oxygen-carbon covalent bonds formed by the condensation of the silanol end and cellulose hydroxyl groups firmly anchor the coupling agent into the paper surface. The ring-opening addition of the epoxy end and the free carboxyl groups of the waterborne polyurethane chain covalently integrates the adhesive film into the same network. During peeling, cracks are forced to bypass and enter the paper matrix. The measured peel strength generally exceeds 22 N / 15 mm, with obvious fiber pull-out and tearing visible on the peel surface. The interface itself becomes the strongest link in the entire laminated system. It should also be noted that the above-mentioned interface covalent anchoring occurs in the bare fiber parts such as the dot gaps, sequence strip intervals, and non-image areas of the halftone image. Based on the measured average coverage of 54.8% ink film in Example 1, approximately 45% of the area is the direct contact area between the adhesive and the pretreated fiber. The covalent anchoring points are distributed in a high-density discrete lattice on the area. The UV-cured ink film coverage area is bonded by the wetting, spreading, and diffusion of the adhesive. The peel crack front is repeatedly pinned and deflected at the discrete anchoring points, and cannot extend in a straight line along any continuous weak interface. It can only be pressed into the paper base. This is in direct contrast to the morphology of the crack smoothly extending along the adhesive-paper interface after the coupling agent was removed in Comparative Example 3.

[0049] To address the survival issue of epoxy groups in a slightly acidic aqueous phase, this invention solves the problem through kinetic window control rather than thermodynamic avoidance, supported by a complete chain of quantitative evidence. The acid-catalyzed ring-opening hydrolysis rate of epoxy is positively correlated with hydrogen ion activity, temperature, and free water content. Therefore, pH adjustment is scheduled before the addition of the two epoxy-containing components, ensuring that the solution is in a weakly acidic environment of pH 2.8 to 3.2 from the moment of addition, rather than the initial strong acid mother liquor near pH 2.0. The solution temperature is lowered to room temperature after the crosslinking agent has dissolved. The working solution is prepared immediately and has a limited 4-hour pot life. Titration tracking in Example 1 shows that the epoxy retention rates of the working solution are 97.8%, 93.6%, and 88.4% immediately after preparation, at 2 hours, and at 4 hours, respectively. After impregnation, the wet paper undergoes a two-stage drying process to remove the majority of free water within one to two minutes. The high-risk window of the coexistence of moisture, heat, and acid is compressed to minutes. Once the free water is removed, the hydrolysis reaction terminates automatically due to the loss of the medium. The epoxy groups then remain in a chemically sealed state in a semi-dry matrix with an absolute moisture content of 4.0% to 5.5% until they are activated in the post-heat curing stage. The extraction titration of the pre-dried paper sample in Example 1 showed an epoxy retention rate of 82.7%. Its infrared difference spectrum with that of the untreated paper retained a clear epoxy characteristic absorption near 910 cm⁻¹. After completing step S4, this absorption basically disappeared, while the ester carbonyl absorption at 1728 cm⁻¹ was simultaneously enhanced. This constitutes direct spectroscopic evidence that the epoxy groups survived to the curing stage and were consumed and bonded in this stage. As for the unavoidable loss of 10% to 20% of epoxy during the solution preparation and drying stages, its hydrolysis product is terminal vicinal diol. The primary and secondary hydroxyl groups contained therein are also esterified by cyclic anhydrides and incorporated into the network in the second stage. This is an equivalent switching of the bonding pathway rather than a net loss of activity, which is one of the reasons why the performance of each embodiment is not sensitive to batch fluctuations in the solution preparation. In conjunction with this, two quantitative criteria are also given for the claim that no substantial crosslinking occurs in step S2: First, after rinsing the pre-dried paper sample with dilute sodium carbonate solution, no ester carbonyl absorption can be detected at 1728 cm⁻¹, indicating that esterification crosslinking has indeed not started; Second, according to inductively coupled plasma atomic emission spectrometry, the hot water extractable silicon of the pre-dried paper sample accounts for 71% of the total silicon content, which drops to 18% after the first stage of 95°C heat treatment. This indicates that the condensation of silanol and cellulose hydroxyl groups only forms a small number of primary anchor points in the pre-drying stage, and its deepening depends on the specific thermal history of the first stage. The functional boundaries of the first stage in steps S2 and S4 are thus experimentally defined.

[0050] Comparative Example 4 demonstrates the irreplaceable nature of the low-temperature window from a process route perspective. When the composite structure is baked at the traditional 170℃ condition, even with the same release cloth and pressure equalization buffer pad, the temperature still far exceeds the glass transition range of 70℃ to 80℃ for polyethylene terephthalate gratings. The lens unit sagitta collapses by nearly 40%, rendering the entire optical function unusable. Simultaneously, the cellulose dehydrates and yellows at high temperatures, its whiteness drops to 67.8, and its tear resistance retention rate is only 51.2%. While the route of first cross-linking the base paper at high temperature before lamination preserves the lens, the active hydroxyl groups on the cross-linked paper surface are blocked and consumed, strong acid residue remains, and the fibers become severely brittle, resulting in a peel strength of less than 7N / 15mm, making it impossible to form a usable product. The comparison shows that only by lowering the deep cross-linking trigger temperature to around 105℃ and completing it after lamination molding can both dimensional stability and optical integrity be achieved in the same product. This is the fundamental difference between this invention and existing technologies.

[0051] Comparative Examples 5 and 4 precisely define the safety boundary mentioned above through experiments in two orthogonal directions of force and heat. The temperature, nominal pressure, and holding time of Comparative Example 5 are consistent with those of Example 1, except that the release cloth and pressure equalization buffer pad are removed and a rigid polished pressure plate directly presses against the cylindrical lens. The initial contact between the pressure plate and the raised ridge is close to line contact, and the actual contact area is only about one-tenth of the nominal area. The local contact stress at the tooth tip is amplified to about ten times the nominal pressure, reaching or even exceeding the high elastic plateau modulus. The tooth tip then undergoes local crushing and lateral flow, and the arc height change rate rises to 4.6%. The imaging shows periodic bright bands corresponding to the contact imprint of the pressure plate. However, its dimensional stability, peel strength, and tear retention rate related to the chemical network are still at the same level as those of Example 1, indicating that the failure of this example is purely within the scope of contact mechanics, and also proving the necessity of the pressure equalization buffer pad as a force transmission medium. Comparative Example 4 shows that the buffer pad cannot withstand the temperature drop. 170°C is about 90°C above the glass transition range. The macroscopic viscosity of the material drops by about five orders of magnitude compared to 105°C according to the time-temperature equivalence relationship. Even if the load has undergone hydrostatic compression, the residual deviatoric stress and the relaxation of the lens's own surface tension are enough to cause the sagittal height to collapse by nearly 40% within 3 minutes. To further calibrate the temperature critical position, the second stage temperature was increased to 115°C and 120°C respectively under all the conditions of Example 1 for retesting. The sagittal height change rate increased accordingly to 3.2% and 7.9%. The flipped image showed a identifiable weakening of the depth of field, confirming that the claim of setting the upper limit of the second temperature at 110°C and the optimal setting at 105°C has clear experimental basis.

[0052] Within the examples, the parameter changes exhibited a pattern consistent with reaction kinetics. In Example 6, the second-stage temperature was reduced from 105°C to 100°C while the holding time remained unchanged. The dimensional change rate increased from 0.05% to 0.09%, and the peel strength decreased from 24.6 N / 15 mm to 22.9 N / 15 mm, indicating that the esterification and ring-opening reaction rates slowed down at 100°C, and the conversion was insufficient within 25 minutes. In Example 2, although the amounts of each component were at the lower limit and the second temperature was also 100°C, all indicators were still fully met after the holding time was extended to 30 minutes, indicating that there is a complementary kinetic relationship between temperature and time within the window defined in the claims. In Example 3, the crosslinking was most complete and the peel strength was the highest among all examples when operating at the upper limit of 110°C, but the lens sagittal height change rate increased to 0.8%, and the whiteness decreased to 82.6, suggesting that further heating would approach the thermal deformation criticality of the grating material and the starting point of thermal yellowing of cellulose. Therefore, 105°C was chosen as the optimal setting that balances production efficiency and safety margin. In Example 5, even after omitting gradient cooling and aging, although the chemical network had already formed, the dimensional change rate and warpage height still increased to 0.11% and 0.9 mm, respectively. This indicates that the residual thermomechanical stress in the interlayer caused by rapid freezing will be slowly released during subsequent damp heat testing. Gradient annealing and constant temperature and humidity aging make independent contributions to eliminating latent warpage. In Example 4, after replacing the paper with low basis weight double-sided offset paper and high pitch thin modified polyethylene terephthalate grating, no systematic degradation was observed in any of the indicators, indicating that this method has good universality for the substrate and grating specification range defined in the claims.

[0053] In summary, this invention addresses the matrix mobility bottleneck by synergistically plasticizing the amorphous regions of cellulose with dimethyl sulfone and bound water. Combined with the nucleophilic acyl transfer catalysis of sodium hypophosphite, the effective trigger temperature for deep esterification crosslinking of cellulose is compressed to the 100°C to 110°C range. Furthermore, the flexible segments of polyglycerol polyglycidyl ether provide toughening, the double-end bridging of epoxy silane coupling agents, and the hydrostatic transfer of the pressure-holding load via a flexible pressure-equalizing buffer pad placed on the lens surface, all contribute to achieving simultaneous matrix dimensional stability, toughness compensation, interfacial covalent bonding, and preservation of the optical microstructure during a single low-temperature hot-pressing process. The removal of any core component or the conventional substitution of the process route leads to a significant deterioration in key performance characteristics. The comprehensive level of various indicators achieved under the complete solution is unattainable by simply combining individual methods, resulting in technical effects that were previously unpredictable.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for thermal stabilization treatment of paper-based cylindrical lenticular lenticular images, characterized in that, Includes the following steps: S1. Preparation of pre-impregnation stabilization solution: Mix polycarboxylic acid crosslinking agent, phosphorus-containing catalyst, dimethyl sulfone, multifunctional water-soluble epoxy resin and pre-hydrolyzed epoxy silane coupling agent in an aqueous medium, adjust the pH of the mixture to be slightly acidic, and obtain the pre-impregnation stabilization solution. S2. In-situ micro-impregnation and sub-activation pre-drying: The paper substrate is impregnated in the pre-impregnation stabilization solution for sizing treatment, and then subjected to gradient pre-drying at a temperature lower than the esterification and cross-linking activation temperature of the polycarboxylic acid cross-linking agent. The absolute moisture content of the paper substrate is controlled so that the effective components in the pre-impregnation stabilization solution adhere to the cellulose surface and enter the amorphous region, and the polycarboxylic acid cross-linking agent does not undergo substantial esterification and cross-linking. S3, Printing and Coating: An interlaced micro-image sequence is printed on the surface of the paper substrate after step S2. A water-based polyurethane adhesive is coated on the printed surface and surface-dried. Then, a cylindrical lens grating with a grating texture is optically aligned with the interlaced micro-image sequence and cold-pressed to obtain a paper-plastic structure. S4. Low-temperature synergistic semi-interpenetrating network post-thermal curing: The paper-plastic structure undergoes a two-stage hot-press curing process, specifically including: First stage heat treatment: Heating is carried out under the first temperature condition to deepen and complete the dehydration condensation reaction between the silanol groups in the epoxy silane coupling agent and the cellulose hydroxyl groups on the surface of the paper substrate. Second-stage heat treatment: A flexible pressure equalizing buffer pad with a release surface is placed on the lens surface of the cylindrical lens grating. Mechanical pressure is applied to the paper-plastic structure and evenly transmitted to the curved surface of the lens through the flexible pressure equalizing buffer pad. Heating is carried out at a second temperature condition that is higher than the first temperature and lower than the thermal deformation limit of the cylindrical lens grating material. Through the hydrogen bond breaking effect of dimethyl sulfone on cellulose and the catalytic effect of the phosphorus-containing catalyst, the polycarboxylic acid crosslinking agent and the cellulose inside the paper substrate are covalently triggered to undergo crosslinking. At the same time, the ring-opening etherification reaction of the multifunctional water-soluble epoxy resin and the cellulose is triggered, and the ring-opening covalent addition reaction of the epoxy group of the epoxy silane coupling agent and the active group in the waterborne polyurethane adhesive is triggered.

2. The method according to claim 1, characterized in that, The polycarboxylic acid crosslinking agent is 1,2,3,4-butanetetracarboxylic acid; The phosphorus-containing catalyst is selected from sodium hypophosphite or sodium hypophosphite monohydrate; The multifunctional water-soluble epoxy resin is a polyglycerol polyglycidyl ether with an aliphatic backbone and at least 4 epoxy groups. The pre-hydrolyzed epoxy silane coupling agent is prepared by hydrolysis of γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

3. The method according to claim 1, characterized in that, In step S1, based on 1000 parts by mass of the aqueous medium, the addition amounts of each component are as follows: 60 to 70 parts by mass of the polycarboxylic acid crosslinking agent, 40 to 50 parts by mass of the phosphorus-containing catalyst, 10 to 20 parts by mass of the dimethyl sulfone, 20 to 30 parts by mass of the multifunctional water-soluble epoxy resin, and 10 to 15 parts by mass of the pre-hydrolyzed epoxy silane coupling agent (calculated based on effective pure material). In step S1, the pH of the mixture is adjusted to the range of 2.8 to 3.2 by adding alkali solution.

4. The method according to claim 1, characterized in that, The pre-hydrolyzed epoxy silane coupling agent is prepared by the following process: γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added dropwise to deionized water with pH adjusted to 4.0 by acid, and the mixture is stirred and hydrolyzed at room temperature for 30 to 45 minutes until the mixture changes from turbid to a transparent homogeneous solution.

5. The method according to claim 1, characterized in that, In step S2, the sizing process is carried out using a two-roll press sizing machine, and the linear pressure of the sizing rolls is controlled to keep the liquid content of the paper substrate between 75% and 80%. The maximum drying temperature of the gradient pre-drying does not exceed 80°C, and the absolute moisture content of the paper substrate is controlled to be between 4.0% and 5.5% at the drying endpoint.

6. The method according to claim 1, characterized in that, In step S3, the waterborne polyurethane adhesive is an anionic waterborne polyurethane dispersion containing free carboxyl groups or free amino groups in its molecular chain segments. The wet adhesive coating amount is controlled so that the dry adhesive weight is 12g / m² to 15g / m². The surface drying treatment is carried out in a hot air environment at 45℃ to 55℃. The lamination pressure during cold pressing is set to 0.5MPa to 0.7MPa, and the lamination pressure is calculated based on the nominal projected area of ​​the contact area of ​​the pressure roller.

7. The method according to claim 1, characterized in that, In step S4, the process conditions for the first stage heat treatment are: working temperature of 90°C to 95°C, and constant temperature for 10 to 20 minutes; the process conditions for the second stage heat treatment are: working temperature of 100°C to 110°C, applied mechanical holding pressure of 0.05 MPa to 0.20 MPa, and constant temperature for 20 to 30 minutes.

8. The method according to claim 7, characterized in that, In step S4, the first temperature of the first stage heat treatment is constant at 95°C, the second temperature of the second stage heat treatment is constant at 105°C, and the mechanical holding pressure is constant at 0.10 MPa.

9. The method according to claim 1, characterized in that, The paper substrate is selected from coated white cardboard or offset paper with a basis weight of 150 g / m² to 250 g / m²; the cylindrical lens grating is extruded from polyethylene terephthalate or modified polyethylene terephthalate, with an optical pitch of 40 LPI to 100 LPI, a material thickness of 0.35 mm to 0.90 mm, and a refractive index greater than 1.

5. The material thickness t and the radius of curvature R and refractive index n of the cylindrical lens satisfy the focal length matching relationship t = nR / (n-1), with a deviation not exceeding ±8%, so that the staggered micro-image sequence is located at the inner focal plane of the cylindrical lens material.

10. The method according to claim 1, characterized in that, Step S4 is followed by step S5: the paper-plastic structure that has completed the low-temperature synergistic semi-interpenetrating network thermal curing treatment is moved into a cooling chamber and gradually cooled to room temperature at a constant cooling rate to relax thermomechanical stress. Then, it is aged in a constant temperature and humidity warehouse environment with a relative humidity of 50% and a temperature of 25°C.